Social distancing cut down the prevalence of acute otitis media in children - Yu, Huiqian; Gu, Dantong; Yu, Fangzhou; Li, Qingzhong (Frontiers in Public Health, 2023)
Objectives: To evaluate the additional, unintended benefits of social distancing in cutting down the prevalence of acute otitis media (AOM) in children, especially during coronavirus disease 2019 (COVID-19) periods. Methods: The daily outpatient attendance of AOM for childhood (from 6 months to 12 years) was compared in the tertiary hospital in Shanghai during pre-COVID-19 and COVID-19 year. Results: A total of 24543 AOM cases were included from 2015 to 2020. When age was taken into account, children in kindergarten (aged 4-6) constitute 66.2% (16236/24543) of all case, followed by primary school students (6441/24543, 26.2%) and preschoolers <3 years old (1866/24543, 7.6%). There was an estimated 63.6% (54.32%-70.36%) reduction in the daily outpatient attendance of AOM associated with the introduction of social distancing in 2020 (COVID-19 year). The epidemic trend of AOM in 2015-2019 was characterized by seasonal fluctuations, with highest incidence in December (18.8%±0.5%) and lower in February (4.5%±0.2%), June (3.7%±0.7%) and August (3.5%±0.5%). And distribution characteristics of different ages in COVID-19 period broadly in line with that in non-pandemic period. Conclusion: Seasonal fluctuation in the prevalence of AOM was observed in pre-COVID-19 period (2015-2019), with a peak in winter and a nadir in summer. The >50% drop of outpatient attendance of AOM in 2020 (COVID-19 year) suggest that social distancing, mask effects and good hand hygiene can significantly reduce the incidence of AOM, which provides a preventive and therapeutic point of view for AOM.